At the Plate with Sammy Sosa - Christopher, Matt; Nang Chan Yeema (New York, USA Little, Brown and Company, 1999)
A biography of the Chicago Cubs power hitter, Sammy Sosa, from his poor childhood in the Dominican Republic to the home run record-breaking 1998 season.
Keywords: Biography